2016
DOI: 10.1002/2016ms000652
|View full text |Cite
|
Sign up to set email alerts
|

Simulating effects of a wind‐turbine array using LES and RANS

Abstract: Growth in wind power production has motivated investigation of wind‐farm impacts on in situ flow fields and downstream interactions with agriculture and other wind farms. These impacts can be simulated with both large‐eddy simulations (LES) and mesoscale wind‐farm parameterizations (WFP). The Weather Research and Forecasting (WRF) model offers both approaches. We used the validated generalized actuator disk (GAD) parameterization in WRF‐LES to assess WFP performance. A 12‐turbine array was simulated using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 63 publications
(70 reference statements)
2
42
0
Order By: Relevance
“…While we have shown that individual wakes in neutrally stratified and stably stratified conditions are unlikely to pose hazards to general aviation aircraft, interactions between wakes could also be explored. Future simulations of wind plants that allow for wake interaction (as in Vanderwende et al, 2016) and larger turbine types could be useful. Our conclusions are drawn from rolling moment calculations, though additional calculations of yawing and pitching moments could also be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While we have shown that individual wakes in neutrally stratified and stably stratified conditions are unlikely to pose hazards to general aviation aircraft, interactions between wakes could also be explored. Future simulations of wind plants that allow for wake interaction (as in Vanderwende et al, 2016) and larger turbine types could be useful. Our conclusions are drawn from rolling moment calculations, though additional calculations of yawing and pitching moments could also be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Representing turbines in LES can be done via actuator disks, where the turbine rotor is represented by a permeable circular disk with uniformly distributed thrust forces (Vermeer et al, 2003;Calaf et al, 2010;Mirocha et al, 2014;Aitken et al, 2014b;Vanderwende et al, 2016) or by actuator lines, which represent the turbine blades as separate rotating lines (Sørensen and Shen, 2002;Porté-Agel et al, 2011;Nilsson et al, 2015). Martínez-Tossas et al (2015) compare actuator-line and actuator-disk models and conclude that they produce similar wake profiles; however, the actuatorline model can generate fine flow structures near the blades such as root and tip vortices that the actuator-disk model cannot.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we have shown that individual wakes in neutrally stratified and stably stratified conditions are unlikely to pose hazards to general aviation 25 aircraft, interactions between wakes could also be explored. Future simulations of wind plants that allow for wake interaction (as in Vanderwende et al (2016)) could be useful. Our conclusions are drawn from rolling moment calculations, though additional calculations of yawing and pitching moments could also be beneficial.…”
mentioning
confidence: 99%
“…Representing turbines in LES can be done via actuator disks, where the turbine rotor is represented by a permeable circular disk with uniformly distributed thrust forces (Vermeer et al, 2003;Calaf et al, 2010;Mirocha et al, 2014;Aitken et al, 2014b;Vanderwende et al, 2016), or by actuator lines, which represent the turbine blades as separate rotating lines (Sørensen and Shen, 2002;Porté-Agel et al, 2011;Nilsson et al, 2015). Martínez-Tossas et al (2015) compare actuator-line and actuatordisk models and conclude that they produce similar wake profiles; however, the actuator-line model can generate fine flow structures near the blades such as root and tip vortices that the actuator-disk model cannot.…”
mentioning
confidence: 99%